2016
DOI: 10.1111/jch.12945
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hypertensive disorders in pregnancy following assisted reproductive technology: overview and meta‐analysis

Abstract: The extent of the increased risk of pregnancy hypertensive disorders following assisted reproductive technology (ART) was investigated. PubMed and the Cochrane Collaboration Library were used as data sources to identify and select longitudinal cohorts comparing pregnancies following ART with spontaneously conceived pregnancies, between 1978 and June 2016. Risk ratios and 95% confidence intervals (CIs) of three outcomes, ie, gestational hypertension (GH), preeclampsia (PE), and their sum (PHD), were calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
(42 reference statements)
5
26
0
Order By: Relevance
“…In a twins study, Fox et al ( 318 ) found, on adjusted analysis, that the egg donation independently associated with PE (aOR 2.409, CI 1.051–5.524). The meta-anaysis of Thomopoulos et al ( 319 ) gave a risk ratio for egg donation of 3.60 (CI 2.56–5.05) over controls, a value similar to that of Blázquez et al ( 320 ). Finally, a recent meta-analysis by Masoudian et al ( 313 ) found that that the risk of PE is considerably higher in oocyte-donation pregnancies compared to other methods of assisted reproductive technology (OR, 2.54; CI 1.98–3.24; P < 0.0001) or to natural conception (OR, 4.34; CI 3.10–6.06; P < 0.0001).…”
Section: Evidence From Epidemiology—semen Can Be Protective Against Psupporting
confidence: 67%
See 1 more Smart Citation
“…In a twins study, Fox et al ( 318 ) found, on adjusted analysis, that the egg donation independently associated with PE (aOR 2.409, CI 1.051–5.524). The meta-anaysis of Thomopoulos et al ( 319 ) gave a risk ratio for egg donation of 3.60 (CI 2.56–5.05) over controls, a value similar to that of Blázquez et al ( 320 ). Finally, a recent meta-analysis by Masoudian et al ( 313 ) found that that the risk of PE is considerably higher in oocyte-donation pregnancies compared to other methods of assisted reproductive technology (OR, 2.54; CI 1.98–3.24; P < 0.0001) or to natural conception (OR, 4.34; CI 3.10–6.06; P < 0.0001).…”
Section: Evidence From Epidemiology—semen Can Be Protective Against Psupporting
confidence: 67%
“…Thomopoulos et al carried out two detailed and systematic reviews ( 319 , 332 ); the latter ( 319 ) covered 7,038,029 pregnancies (203,375 following any invasive ART) and determined that the risk of PE was increased by 75% (95% CI 50–103%).…”
Section: Evidence From Epidemiology—semen Can Be Protective Against Pmentioning
confidence: 99%
“…Third, the information of assisted reproductive technology pregnancies (ref. 34 ) and a history of sleep apnea (ref. 35 ) were not available in the present study; therefore, it should be cautious when generalizing the findings.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective stratified analysis of ART (596,520 mothers; 30.6% ART mothers) indicated that multiple pregnancies after ART are the single most likely explanation for the increased rate of gestational hypertension or preeclampsia among ART mothers [83]. More recently, a meta-analysis including 66 longitudinal studies (7,038,029 pregnancies; 203,375 following any ART) found that all pregnancy-related hypertensive disorders, independent of gestation order, were increased following any invasive ART [+54% (95% CI: 39%-70%), gestational hypertension +79% (95% CI: 24%-157%), and preeclampsia +75% (95% CI: 50%-103%)] [84].…”
Section: Assisted Reproductive Technologies (Art)mentioning
confidence: 99%